News search, blogs and feeds : a toolkit - Vage, Lars (Chandos information professional series., 2010)
News Search, Blogs and Feeds addresses both the needs of professionals, with a strategic need of monitoring the surrounding world, and users, with a need to find the best news sources, monitoring services and news search strategies. This practical handbook provides an analysis of readily available tools including the use of social networks for news discovery and commercial news search databases. It is an essential reference for information professionals in this field as well as librarians and library and IT managers.